Diagnostic utility of serum biomarkers in large vessel vasculitis and their correlation with positron emission tomography - Bilici Salman, Reyhan; Koca, Gülce; Gülbahar Ateş, Seda; Yapar, Dilek; Babaoglu, Hakan; Satış, Hasan; Avanoglu Güler, Aslıhan; Karadeniz, Hazan; Ataş, Nuh; Küçük, Hamit; Akdemir, Ümit Özgür; Haznedaroğlu, Şeminur; et al. (Modern rheumatology, 2022)
To investigate the association between vascular inflammation, as detected by positron emission tomography (PET) imaging and interleukin-6 (IL-6), pentraxin3, and B-cell-activating factor (BAFF) in subjects with LVV. The study included newly diagnosed giant cell arteritis (GCA, n = 27) or Takayasu arteritis (n = 9) patients and healthy control (HC, n = 31) subjects. PET scan and blood samples were obtained before the introduction of treatments. IL-6, PTX3, and BAFF levels were determined quantitatively by enzyme-linked immunosorbent assay kits. Thirty-six patients with LVV (20 females, 16 males; age 64.5 ± 16.6 years) and 31 HC (14 females, 17 males; age 37.1 ± 9.6 years) were included. Serum levels of IL-6, PTX3, and BAFF were increased in patients with newly diagnosed LVV compared with healthy control subjects. In receiver operating characteristics (ROC) analysis, serum IL-6 and BAFF provided excellent discrimination of newly diagnosed LVV patients from HC (area under the ROC curve of >0.90 and >0.80, respectively). None of the inflammatory markers correlated with vascular inflammatory activity determined by PET scanning. Our results suggest that IL-6 and BAFF may serve as markers of large vessel vasculitis, while PTX3 is not useful. None of the inflammatory markers correlated with PET assessed vasculitis activity.